Negara Madinah : refleksi tentang agama dan pluralisme - Al Chaidar, 1969-; Sahrasad, Herdi (Yogyakarta : Madani Press, 2000)
Political values of state, nation, etc. according to the Islamic Madinah Constitution
Includes bibliographical references (p. 85-87) and index
Keywords: Islam and politics -- Indonesia; Indonesia -- Politics and government -- 1998-